Pengaruh Fraksi Massa Serat Pada Greencomposite Serat Daun Nanas dan Sari Pati Kentang Terhadap Kemampuan Peredaman Suara dan Porositas - Jagjiwen, Jagjiwen; Kencanawati, Cok Istri Putri Kusuma; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract The use of materials such as petroleum-based plastics, heavy metals, and concrete has been widespread in various applications, from construction to manufacturing. However, these materials can have negative environmental impacts. Natural fiber-based composites, such as pineapple leaf fiber and potato starch, offer a more environmentally friendly alternative. This study examines the sound absorption properties of a greencomposite made from two components: potato starch as the matrix and pineapple leaf fiber as the reinforcement, using the impedance tube method. The test results show that the pineapple leaf fiber composite with a 5% fiber fraction and fiber lengths of 0.5 cm and 1 cm has the highest sound absorption coefficient (? 0.24) at 400 Hz. Meanwhile, the 15% fiber composite with 1 cm fiber length is the most effective and stable sound-absorbing material in the frequency range of 1200 Hz to 4000 Hz. The effect of varying the pineapple fiber mass fraction on the specimen's porosity was demonstrated by a consistent increase in porosity with fiber lengths of 0.5 cm and 1 cm, showing values of 41.3%, 42.7%, 44.4%, and 44.5%, 44.9%, 45.6%, respectively. This indicates that higher fiber mass fractions lead to greater porosity in the specimens. Keywords: Greencomposite, Pineapple Fiber, Potato Starch, Fiber Mass Fraction, Acoustic Testing, Porosity, Sound Absorption